2017
DOI: 10.1093/pm/pnx286
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Prognostic Genicular Nerve Blocks to Determine the Predictive Value for the Outcome of Cooled Radiofrequency Ablation for Chronic Knee Pain Due to Osteoarthritis

Abstract: This study demonstrated clinically meaningful improvements in pain and physical function up to six months following cRFA. A prognostic genicular nerve block using a local anesthetic volume of 1 mL at each injection site and a threshold of ≥ 50% pain relief for subsequent cRFA eligibility did not improve the rate of treatment success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 38 publications
2
57
1
11
Order By: Relevance
“…The complexity of the knee joint’s innervation has resulted in a disparity in procedural technique among the available controlled and observational studies. Studies report on a range of procedural targets to include the SM, IM, and SL genicular nerves in combination, 28 33 the saphenous nerve, 34 the sciatic nerve, 35 the IP genicular nerve, 36 the IP and SM genicular nerves in combination, 37 the femoral, tibial, saphenous nerves, and peripatellar plexus in combination, 38 and the intra-articular joint space 6 , 25 , 39 41 ( Figures 1 and 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity of the knee joint’s innervation has resulted in a disparity in procedural technique among the available controlled and observational studies. Studies report on a range of procedural targets to include the SM, IM, and SL genicular nerves in combination, 28 33 the saphenous nerve, 34 the sciatic nerve, 35 the IP genicular nerve, 36 the IP and SM genicular nerves in combination, 37 the femoral, tibial, saphenous nerves, and peripatellar plexus in combination, 38 and the intra-articular joint space 6 , 25 , 39 41 ( Figures 1 and 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 2017 randomized trial by McCormick et al also employed CRFA, but the study was designed to determine the predictive value of pre-RFA nerve blocks, not to compare RFA to other modalities. 33 Fifty-four patients with chronic knee pain due to OA all received CRFA, but 29 did so after prognostic blocks and 25 did not. Notably, only three of 32 (9.3%) patients had a negative block, defined as <50% pain relief.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At final follow-up (6-12 months), all patients reported at least an 80% improvement in knee pain and no patients went on to TKA. While the findings of this report are limited by sample size, when viewed in conjunction with the work from McCormick et al, 39 it appears that a robust response to the prognostic nerve block may be indicative of greater likelihood for clinical success following C-RFA.…”
Section: C-rfa Treatment For Knee Oa: Evidence and Outcomesmentioning
confidence: 53%
“…Rajiv et al [24] administered unilateral or bilateral cRFA in four patients with pain relief of 80% from the diagnostic genicular nerve block before the ablation, and reported improvements by 80-100% in knee pain, function and using analgesic drugs at six to 12-month follow up in all patients. Mc Cormick et al [25] showed clinically significant improvement concerning pain, physical function, and psychologic function up to approximately six months in about half of the patients who underwent genicular nerve cRFA for chronic pain associated with knee osteoarthritis. The authors underlined that a prognostic genicular nerve block used as a threshold of 50% pain relief for conformity of 1 mL local anesthetic volume and subsequent cRFA in each injection region did not improve the rate of treatment success.…”
Section: Discussionmentioning
confidence: 99%